2023
DOI: 10.1021/acs.jafc.3c04865
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Cytochrome P450s in the Fat Body and Malpighian Tubules of the Polyphagous Pests of Spodoptera litura Confer Xenobiotic Tolerance

Jianyi Li,
Long Jin,
Yuntong Lv
et al.

Abstract: Cytochrome P450 plays vital roles in detoxifying xenobiotics. In this study, SlCYP340A and SlCYP340L expression in the Spodoptera litura fat body and SlCYP332A1, SlCYP6AB12, SlCYP6AB58, SlCYP6AB59, and SlCYP6AN4 expression in the Malpighian tubules were significantly upregulated after cyantraniliprole exposure, and SlCYP6AB58 and SlCYP6AB59 expression levels were simultaneously increased in the Malpighian tubules after gossypol treatment. Drosophila ectopically expressing candidate P450 genes showed that SlCYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Among these CYP3 genes, several P450s identified in our previous study were related to cross-tolerance to cyantraniliprole and gossypol. 42 In addition, we found that a highly abundant CYP9 gene, SlCYP9A75a, shared the highest similarity with its paralogues SlCYP9A75b, clustering into the same branch with other CYP9A genes of S. frugiperda and S. exigua, which were involved in detoxifying insecticides and plant secondary metabolites (Figure 3A). 13 A previous study has demonstrated that SlCYP9A75a and SlCYP9A75b were significantly upregulated after abamectin exposure and has determined that these two genes contributed to abamectin tolerance via transgenic Drosophila bioassays.…”
Section: ■ Discussionmentioning
confidence: 88%
“…Among these CYP3 genes, several P450s identified in our previous study were related to cross-tolerance to cyantraniliprole and gossypol. 42 In addition, we found that a highly abundant CYP9 gene, SlCYP9A75a, shared the highest similarity with its paralogues SlCYP9A75b, clustering into the same branch with other CYP9A genes of S. frugiperda and S. exigua, which were involved in detoxifying insecticides and plant secondary metabolites (Figure 3A). 13 A previous study has demonstrated that SlCYP9A75a and SlCYP9A75b were significantly upregulated after abamectin exposure and has determined that these two genes contributed to abamectin tolerance via transgenic Drosophila bioassays.…”
Section: ■ Discussionmentioning
confidence: 88%
“…gossypii, further functional investigations of their roles in neonicotinoid detoxification are needed. The GAL4/UAS system has been widely used to explore the roles of detoxification genes in insect resistance in transgenic Drosophila in vivo. Overexpressing UGT33J17 and UGT41D10 of S. litura in Drosophila reduced the indoxacarb toxicity to flies .…”
Section: Discussionmentioning
confidence: 99%
“…Further details of the bioassays used are provided in our previous study. 31 The median lethal dose (LD 50 ) and 95% fiducial limits were calculated by probit analysis using SPSS Statistics (IBM SPSS Statistics 26 software, Chicago, IL, USA) and PoloPlus 2.00 software (LeOra Software, USA).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Topical application (F1 of the UAS- CYP6CY22 and Act5C-GAL4 hybrids) and feeding (F1 of the UAS- CYP6CY22 and Esg-GAL4 hybrids) methods were used to assess the susceptibility of straight-wing-phenotype adult female flies to cyantraniliprole. Further details of the bioassays used are provided in our previous study . The median lethal dose (LD 50 ) and 95% fiducial limits were calculated by probit analysis using SPSS Statistics (IBM SPSS Statistics 26 software, Chicago, IL, USA) and PoloPlus 2.00 software (LeOra Software, USA).…”
Section: Methodsmentioning
confidence: 99%